Asthma Across Age: Insights From Primary Care - Kaplan, Alan; Hardjojo, Antony; Yu, Shaylynn; Price, David (Frontiers in Pediatrics, 2019)
Asthma is a heterogeneous disease comprising of multiple phenotypes which affect patients from childhood up to old age. In this review, we summarize the current knowledge on the similarity and differences in asthma across different age-group, with emphasis on the perspective from primary care. Despite the similar presentation of the disease, phenotyping studies showed that there are differences in the distribution of phenotypes of asthma presenting in childhood compared to adulthood. Whereas asthma with early age of onset tends to be of the atopic phenotype, the disease shifts towards the non-atopic phenotypes at later ages. Studies within primary care patients aiming to elucidate risk factors for future asthma exacerbation have shown pediatric and elderly patients to be at higher risk for future asthma attacks compared to other adult patients. Regardless, both pediatric and adult studies demonstrated previous asthma episodes and severity, along with high blood eosinophil to predict subsequent asthma attacks. Differences in childhood and adult asthma are not limited to the underlying phenotypes but also extends to the challenges in the diagnosis, treatment, and management of the disease. Diagnosis of asthma is complicated by age-specific differential diagnoses such as infectious wheezing and nasal obstruction in children, and aging-related problems such as heart disease and obesity in the elderly. There are also age-related issues leading to decreased disease control such as non-adherence, tobacco use, difficulty in using inhalers and corticosteroid-related side effects which hinders asthma control at different patient age-groups. Several clinical guidelines are available to guide the diagnosis and drug prescription of asthma in pediatric patients. However, there are conflicting recommendations in diagnostic tools and treatment for pediatric patients, posing additional challenges for primary care physicians in working with multiple guidelines. While tools such as spirometry and peak flow variability are often available in primary care, their usage in preschool patients are not consistently recommended. FeNO measurement may be a valuable non-invasive tool which can be adopted by primary physicians to assist asthma diagnosis in preschool-age patients